Impact of Information Society Research in the Global South - Chib, Arul.; May, Julian; Barrantes, Roxana; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2015)
The second volume in the SIRCA book series investigates the impact of information society initiatives by extending the boundaries of academic research into the realm of practice. Global in scope, it includes contributions and research projects from Asia, Africa and Latin America. The international scholarly community has taken a variety of approaches to question the impact of information society initiatives on populations in the Global South. This book addresses two aspects Impact of research: How is the research on ICTs in the Global South playing a role in creating an information society? (e.g. policy formulation, media coverage, implementation in practice) and Research on impact: What is the evidence for the impact of ICTs on society? (i.e. the objectives of socio-economic development). This volume brings together a multiplicity of voices and approaches from social scientific research to produce an engaging volume for a variety of stakeholders including academics, researchers, practitioners, policy-makers and those in the business and civil sectors of society.
Foreword -- Chapter 1: Research on Impact of the Information Society in the Global South: An Introduction to SIRCA -- Part I: Impact of Research -- Chapter 2. The Impact of Research on Development Policy and Practice: This Much We Know -- Chapter 3: Constructing Theories of Change for Information Society Impact Research -- Chapter 4: A New Set of Questions: ICT4D Research and Policy -- Chapter 5: Progress Towards Resolving the Measurement Link Between ICT and Poverty Reduction -- Chapter 6: The Impact of mFinance Initiatives in the Global South: A Review of the Literature -- Chapter 7: An Analytical Framework to Incorporate ICT as an Independent Variable -- Part II: Research on Impact -- Chapter 8: (Un)Balanced Conversations: Participatory Action Research in Technology Development in Peruvian Primary Schools -- Chapter 9: The Institutional Dynamics Perspective of ICT for Health Initiatives in India -- Chapter 10: Cybersex as Affective Labour: Critical Interrogations of the Philippine ICT Framework and the Cybercrime Prevention Act of 2012 -- Chapter 11: The Internet and Indonesian Women Entrepreneurs: Examining the Impact of Social Media on Women Empowerment -- Chapter 12. The Use of Mobile Communication in the Marketing of Foodstuffs in Côte d Ivoire -- Chapter 13: Designing Web 2.0 Tools for Online Public Consultation -- Chapter 14: ICTs and Opinion Expression: An Empirical Study of New Generation Migrant Workers in Shanghai -- Chapter 15: Impact of Research or Research on Impact: More Than a Matter of Semantics and Sequence.
Keywords: Social sciences; Economic policy; Communication; Social Sciences; Communication Studies; Information Systems Applications (incl. Internet).; R & D/Technology Policy; Electronic books